Learning Islamic Religious Education Based On Local Wisdom Assisted By Animated Videos In Increasing The Learning Motivation Of Elementary School Students - Herawati, Enok Tati Herni; Rukajat, Ajat; Mansyur, Masykur H; Kejora, Muhamad Taufik Bintang (Papanda Publisher, 2025)
This study aims to explore the application of Islamic Religious Education (PAI) learning based on local wisdom using animated videos in class V of SDN Mulyasejati IV, Ciampel, Karawang, to increase students' learning motivation. The approach used is qualitative with the descriptive method of exploratory case studies, which allows data collection through interviews, participatory observations, and documentation. The main data sources are PAI teachers and grade V students. This study found that the use of animated videos that relate Islamic teachings with local traditions such as earth alms and gotong royong is very effective in attracting attention and increasing students' understanding of teaching materials. As a result, there is an increase in students' motivation to learn which can be seen from their active involvement in learning. The implication of this research is that the integration of technology-based media, such as animated videos, can be an effective tool to enrich students' learning experiences and make them more relevant to their daily lives. However, this research also faces limitations in access to technology and teachers' ability to manage technology-based learning media. The suggestions put forward are the need for more intensive training for teachers and improved technology facilities in schools to support more interactive and contextual learning